2013
DOI: 10.1186/1475-925x-12-26
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pressure and padding on motion artifact of textile electrodes

Abstract: BackgroundWith the aging population and rising healthcare costs, wearable monitoring is gaining importance. The motion artifact affecting dry electrodes is one of the main challenges preventing the widespread use of wearable monitoring systems. In this paper we investigate the motion artifact and ways of making a textile electrode more resilient against motion artifact. Our aim is to study the effects of the pressure exerted onto the electrode, and the effects of inserting padding between the applied pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
102
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(106 citation statements)
references
References 31 publications
3
102
0
1
Order By: Relevance
“…The most commonly used electrode for ECG monitoring is a gel-type silver/silver chloride (Ag/AgCl) electrode. However, as some pathologies require extended monitoring during the patient's normal activities, interest in mobile and long-term monitoring has grown for diagnosis, screening, risk assessment, prevention, and rehabilitation [2]. Wet electrodes are limited in their long-term use because they can irritate the skin.…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly used electrode for ECG monitoring is a gel-type silver/silver chloride (Ag/AgCl) electrode. However, as some pathologies require extended monitoring during the patient's normal activities, interest in mobile and long-term monitoring has grown for diagnosis, screening, risk assessment, prevention, and rehabilitation [2]. Wet electrodes are limited in their long-term use because they can irritate the skin.…”
Section: Introductionmentioning
confidence: 99%
“…The motion artefact interference may be caused by eventual pulling from the cables, but the main source is due to the change of potential across the epidermis during skin deformation by stretching and/or induced by applied pressure [36]. Electrical equivalent models of the electrode-skin interface of gel and textile electrodes have been proposed [31,32,[35][36][37]. The gel electrode model includes the contribution of an electrolyte half-cell potential and the epidermis potential.…”
Section: Resultsmentioning
confidence: 99%
“…The amount of pressure applied on the electrode-skin contact surface also affects the electrode's performance. High pressure lowers the impedance contact and restricts the motion by friction of the electrodes [30,31,36]. Figure 11 shows ECG signals obtained from two Holter exams realized in a hospital environment with an internal patient; in one exam, the patient was wearing the cardio surveillance t-shirt system, while the other used gel electrodes taped to the thorax.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Normal electrodes use adhesive collars or suction cups to stabilize this interface, but for textile electrodes the fit and placement of the sensor are parameters to optimize. Comert et al [25] have investigated how different paddings and pressures applied to the electrode improve the detectability of R-waves in a ECG recorded with textile electrodes. The outcome of the study indicated that by padding the electrode, it stabilizes the electrode-skin contact and improves the R-wave detectability.…”
Section: Electrode Placement/displacementmentioning
confidence: 99%